How perennials survive the droughts: pulse-reserve dynamics in a hyperarid basin - Babad, Avshalom; Bubenzer, Olaf; Hecht, Stefan; Groner, Elli (Ecohydrology, 2025)
The hyperarid environment poses significant challenges to local vegetation. The main limiting factors are water scarcity and inconsistent precipitation regimes. Nevertheless, perennials flourish in hyperarid stream channels, predominantly acacia trees, which require significant amounts of water. This study seeks to reveal the mechanism that provides acacias with adequate water. Although the pulse-reserve model can explain how desert flora survives, hyperarid environments are much more complicated. Accordingly, direct rainfall is insufficient to sustain local perennials, which rely on runoff for their water source. The hyperarid Gvanim basin in southern Israel is a small watershed that supports many perennials, including a thriving population of acacia trees. High-resolution hydrological monitoring, including rain, evaporation, soil water content and flash flood discharge, along with surveys of lithology and acacia populations, allowed us to calculate the water balance for the basin and quantify the components of the pulse-reserve system. The results indicate that unique geological settings can retain runoff water from a single significant flash flood that is sufficient to sustain perennials even during drought years. We propose a modified pulse-reserve mechanism that provides water to large acacia trees during the hot dry summer in hyperarid areas.